House hold and collective responses to the absence of electricity supply in informal settlements in Johannesburg: a case study of Msawawa and Kya Sands - Nxumalo, Feza Hugh (My University, 2018)
The South African Constitution gives every citizen a right to basic services, and this exclude electrification of every households. It covers basic human rights, and articulates them as Water, and Sanitation. The Department of Energy recognises electrification as basic right through electrification categories provided for informal settlements dwellers. However, many households in informal settlements live without electricity. This research is a case study of Kya Sands and Msawawa informal settlements, two informal settlements on the north western outskirts of Johannesburg that are not connected to formal electricity supply. It explores how their communities respond to the absence of electricity. The study took a qualitative approach based on interviews with residents, business owners and leaders of Msawawa and Kya Sands informal settlements. The finding is that household responses differ across the two informal settlements, in part depending on the strategy adopted by the informal settlement community and the leadership, and in part determined by the sources of energy or fuel in the area. This research reveals a variety of energy sources, and questions the common perception that all informal settlement dwellers have informal electricity connections.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Masters of the Built Environment in the Field of Housing, Johannesburg, 2018.
Keywords: Electric power systems--Management; Electric power distribution; Electric circuits; Electric utilities--Cost control